2021
DOI: 10.1130/g47985.1
|View full text |Cite
|
Sign up to set email alerts
|

Redefining East African Rift System kinematics

Abstract: East African Rift System plate geometries and surface motions are some of the least constrained in the context of global plate motion models. In this study, we used GPS data to constrain Somalian plate rotation and to suggest a new tectonic plate geometry for the region. In addition, we tested geologic data from the Southwest Indian Ridge and new GPS data on Madagascar to determine refined kinematics of the Lwandle microplate. A zone of broad deformation was discovered, extending from the eastern boundary of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
73
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(89 citation statements)
references
References 22 publications
6
73
0
Order By: Relevance
“…The direction of extension along the MER was reconstructed by several authors based on structural data and GPS vectors, suggesting a direction of horizontal stretching ranging between N135°E and N105°E [e.g., Chorowicz et al, 1994, Bilham et al, 1999, Chu and Gordon, 1999, Acocella et al, 2002. Nonetheless, other studies suggested a partly different extension direction trending around N90°-100°[e.g., Bonini et al, 1997, Boccaletti et al, 1998, Fernandes et al, 2004, Pizzi et al, 2006, Agostini et al, 2011b, Saria et al, 2014, Stamps et al, 2021. It is well known that elongated calderas may reflect the regional stress field [e.g., Bosworth et al, 2000Bosworth et al, , 2003 and thus extension along the MER may have controlled caldera elongation [Casey et al, 2006].…”
Section: Discussion: Interaction Between Calderas and Regional Tectonics In The Mermentioning
confidence: 99%
“…The direction of extension along the MER was reconstructed by several authors based on structural data and GPS vectors, suggesting a direction of horizontal stretching ranging between N135°E and N105°E [e.g., Chorowicz et al, 1994, Bilham et al, 1999, Chu and Gordon, 1999, Acocella et al, 2002. Nonetheless, other studies suggested a partly different extension direction trending around N90°-100°[e.g., Bonini et al, 1997, Boccaletti et al, 1998, Fernandes et al, 2004, Pizzi et al, 2006, Agostini et al, 2011b, Saria et al, 2014, Stamps et al, 2021. It is well known that elongated calderas may reflect the regional stress field [e.g., Bosworth et al, 2000Bosworth et al, , 2003 and thus extension along the MER may have controlled caldera elongation [Casey et al, 2006].…”
Section: Discussion: Interaction Between Calderas and Regional Tectonics In The Mermentioning
confidence: 99%
“…Eventually, these variabilities may lead to offset rift propagation from opposite directions. Examples of offset rift systems exist along rifted margins, such as in the South Atlantic (Heine et al., 2013), the Jan Mayen microcontinent in the Norwegian‐Greenland Sea (Gernigon et al., 2012), and in the present‐day East African and Red Sea Rift System (Calais et al., 2006; Eagles et al., 2002; Stamps et al., 2008; Stamps et al., 2021). The strike‐perpendicular offset is likely an important factor in how rift segments eventually link, and the structural features that form in response (Allken et al., 2012; Gerya, 2013a).…”
Section: Introductionmentioning
confidence: 99%
“…(b) Our plate angular velocity solution showing the movement of sites used to define the San (yellow shading) and Rovuma (blue shading) relative to stable Nubia (red shading), and the Euler poles from our velocity solution. Orange lines are plate boundaries (adapted fromDaly et al, 2020;Saria et al, 2013;Stamps et al, 2020).…”
mentioning
confidence: 99%
“…(b) Our plate angular velocity solution showing the movement of sites used to define the San (yellow shading) and Rovuma (blue shading) relative to stable Nubia (red shading), and the Euler poles from our velocity solution. Orange lines are plate boundaries (adapted from Daly et al, 2020;Saria et al, 2013;Stamps et al, 2020). East residual (mm yr −1 ) ITRF14 Nubia residuals −5000 0 5 000 Elevation (m) proposed additional microplates in southern and eastern Africa (Victoria, Rovuma, and Lwandle) based on bands of earthquakes and active faults along edges of the cratons (Calais et al, 2006;Hartnady, 2002;Horner-Johnson et al, 2007;Stamps et al, 2008), as well as zones of diffuse deformation inconsistent with rigid plates (Stamps et al, 2020).…”
mentioning
confidence: 99%
See 1 more Smart Citation